Seaweed community from Intertidal area of satang Besar Island, Sarawak - Nur Iliyana, Binti Mohd.Jusoh (Universiti Malaysia Sarawak (UNIMAS), 2012)
An assessment of seaweed composItion in intertidal zones of Satang Besar Island was done to address the inadequate information of seaweeds for this island. Seaweed samples were collected from 10 stations around the island. Nine genera namely Halimeda, Blyopsis, Avrainvillea, Padina, Sargassum, Halymenia, Acanthophora. Gracilaria and Polysiphonia were identified on the basis of morphological characters. Based on the total number of species, Chlorophyta division showed the highest percentage during the entire period ofstudy. Physicochemical data were carried out and measured from 10 stations at the intertidal zones from Satang Besar Island. The water temperature ranged from 30.1 °C to 33.8 0c. pH ranged from 7.12 to 10.8 and dissolved oxygen (DO) ranged from 6.21 to 8.18 mg/L. All the physicochemical parameters were at suitable level to support seaweed growth. Nutrients like nitrate and orthophosphate varied from 0.02 to 0.47 mg/L and 0.11 to 0.35 mglL respectively. The highest species diversity (H' == 10.20) value was found in station 10 comprising of both rocky shore and sandy beach. Correlation of salinity and pH showed positive relation to species diversity which indicated as important factors for seaweed growth. The distinction in total species number from all stations suggested that different locations and type ofsubstratum may lead to disparity in composition ofseaweeds.